Synthesis and characterization of polypropylene glycol-graft-styrene - Negim, E.; Konysbay, А.М.; Irmukhametova, G.; Kalugin, S.N. (Kompleksnoe Ispolzovanie Mineralnogo Syra = Complex use of mineral resources, 2021)
Grafting polymerization based on polypropylene glycol (PPG) and styrene (St) was synthesized with different composition of styrene using the free radical technique in the presence of potassium persulphate as an initiator. The grafted copolymers (PPG-g-St) used different styrene composition (65/15, 65/25, 65/35), respectively. The grafted copolymers were investigated through FTIR (Fourier-transform spectroscopy), Differential scanning calorimeter and thermogravimetric analyzer. FTIR showed new peaks at 1450 cm-1 and 1135 cm-1 due to the grafting process of St on PPG. Thermal stability of grafted copolymer increases by increasing the ratio of styrene, while Tg decreases by increasing the ratio of styrene.